A Study of Behavior and Satisfaction of Users in Service Marketing Mix in Nakhon Ratchasima Large Private Hospitals - Banhan, Kittiya; Panomjerasawat , Jaruwan (Ratchaphruek Journal, 2021)
This research aimed to study behavior in using services and satisfaction of users in service marketing mix of large private hospitals in Nakhon Ratchasima Province. The sample group was participants who used services in large private hospitals in Nakhon Ratchasima Province, namely Porphat Hospital, St. Mary’s Hospital and Bangkok Ratchasima Hospital, totaling 384 persons. The questionnaire was used as the research instrument. The accidental sampling method was utilized to recruit samples. Statistics for data analysis included frequency, percentage, average, standard deviation, t-test, ANOVA and Scheffe analysis. The research results showed that in large private hospitals in Nakhon Ratchasima Province, most of them has out-patient services. The results of the satisfaction in the service marketing mix of users in large private hospitals in Nakhon Ratchasima province overall was the high level and were most satisfied with their physical appearance. The results of comparing satisfaction were found that the users’ behavior was different. In the department that used the service on the reasons for choosing the service. The hospitals’ services and the type of payment were considered. There would be satisfaction with the different service marketing mixes of the private hospitals in Nakhon Ratchasima Province overall was statistically significant at the .05 level